2016
DOI: 10.1186/s12929-016-0242-7
|View full text |Cite|
|
Sign up to set email alerts
|

Significance of the urokinase-type plasminogen activator and its receptor in the progression of focal segmental glomerulosclerosis in clinical and mouse models

Abstract: BackgroundsuPAR biomarker generally considered a pathogenic factor in FSGS. However, studies have been published that dispute this conclusion. The current study was designed to investigate the roles of uPA and suPAR in FSGS in clinical and mouse models.MethodsClinical subjects including those with biopsy-proven FSGS and MCD were enrolled. To verify the role of uPA in FSGS, Adriamycin was used to induce FSGS in uPA knockout (uPA−/−) and BALB/c (WT) mice. Proteinuria and suPAR, the cleaved/intact forms of the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
7
0
6
Order By: Relevance
“…Thus, 364 studies were initially included, among which 306 studies were excluded after reading the title and abstract. After reading the full text, another 29 studies were excluded; therefore, 29 studies were finally included 9–11 21–46. A flow chart of the study selection process is presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 364 studies were initially included, among which 306 studies were excluded after reading the title and abstract. After reading the full text, another 29 studies were excluded; therefore, 29 studies were finally included 9–11 21–46. A flow chart of the study selection process is presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In a total of 19 studies,9 22 24–28 30 31 33–35 37 38 40 42 44–46 the concentrations of suPAR in primary FSGS and MCD were compared, and the results showed that the concentration of suPAR in primary FSGS was significantly higher compared with that in MCD (p<0.001; SMD: 1.72; 95% CI 1.17 to 2.28; I 2 =94.0%) (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Уровень uPAR в здоровом организме вполне стабилен, но при раке повышается, т. к. uPAR конкурирует с uPA за участие во многих непротеолитических биологических процессах, таких как миграция, адгезия и пролиферация клеток, ангиогенез [22].…”
Section: Discussionunclassified
“…Несмотря на то что экспрессия системы uPA наблюдается как на раковых клетках, так и на поддерживающей строме, на опухолевых клетках она выше, что и объясняет их биологическую агрессивность, эти показатели весьма актуальны для прогностических результатов [20][21][22]. Система uPA является важным прогностическим маркером при различных онкологических заболеваниях, ее определение уже рекомендуют к включению в рутинную клиническую практику [11], однако этот вопрос не исследовался при перитонеальном распространении рака желудка.…”
unclassified
“…After arrival, 6‐week‐old female Balb/c mice (LASCO, Taipei, Taiwan) were randomly allocated to groups of four in macrolon II cages. Experimental FSGS was induced by intravenous administration of AD (Selleckchem, Houston, TX) at a dose of 10 mg/kg as previously described . This study was approved by the Animal Experimentation Ethical Committee of Taipei Medical University.…”
Section: Methodsmentioning
confidence: 99%